(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The rapid expansion of the Internet of Things (IoT) has transformed modern communication by enabling billions of interconnected smart devices to exchange information across heterogeneous wireless networks. IoT technologies have become fundamental to smart cities, healthcare systems, industrial automation, intelligent transportation, environmental monitoring, smart homes, and precision agriculture. Despite these advancements, IoT networks remain highly vulnerable to cyber threats because of their decentralized deployment, constrained computational resources, limited storage capacity, heterogeneous communication protocols, and reliance on centralized authentication mechanisms. Common security threats include unauthorized device access, identity spoofing, distributed denial-of-service (DDoS) attacks, replay attacks, data tampering, malicious firmware modification, eavesdropping, and privacy leakage. Traditional security solutions often rely on centralized servers or certificate authorities, creating single points of failure and limiting scalability in large-scale IoT deployments. The emergence of blockchain technology following the publication of the Bitcoin protocol in 2008 introduced a decentralized, tamper-resistant distributed ledger capable of maintaining secure transaction records without centralized trust. Between 2016 and 2018, researchers increasingly recognized blockchain as a promising technology for enhancing IoT security through decentralized authentication, distributed identity management, immutable data storage, cryptographic verification, and secure communication. The combination of blockchain and IoT offers opportunities to establish trustworthy communication channels while improving data integrity, transparency, resilience, and device authentication in resource-constrained environments. Nevertheless, blockchain integration introduces challenges related to computational overhead, consensus latency, scalability, storage requirements, and energy consumption, requiring lightweight blockchain architectures tailored specifically for IoT networks.